Labiogingival groove: A rare developmental tooth anomaly - Shiva Chauhan; Chahat Puri; Vikas Jindal; Divya Jaggi; Jyoti Gupta (Wolters Kluwer Medknow Publications, 2017)
Labiogingival groove is a congenital morphologic dental anomaly, in which an infolding of the inner enamel epithelium and Hertwig's epithelial root sheath create a groove extending varying depth into root. Epithelial attachment can be breached by gingival irritation secondary to plaque accumulation creating a periodontal defect that spreads to the pulp causing primary periodontal/secondary endodontic. A 12-year-old boy reported with the complaint of painful tooth with pus discharge from labial gingival surface in the maxillary right lateral incisor for 4 months. Intraoral examination revealed bluish red gingiva with loss of contour in relation to maxillary right lateral incisor and purulent discharge in relation to it. A provisional diagnosis of localized gingival abscess in relation to maxillary right incisor (primary periodontic and secondary endodontic involvement) was given, and required treatment was carried out. On exposure of the involved tooth, a labiogingival groove was noticed which could have been a contributing factor for the progression of the condition.